Enhancing SME Success: Exploring the Nexus of Marketing Capability, Product Innovation, and Financial Performance - Suleman, Dede (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
Abstract: This study investigates the relationships between marketing capability, product innovation, and financial performance in small and medium-sized enterprises (SMEs). Data were collected from a diverse sample of 50 SMEs operating across various industry sectors in Mataram City, West Nusa Tenggara. Participants were selected using stratified sampling to ensure representation across different demographic groups. The measurement scales for marketing capability, product innovation, and financial performance were adapted from established instruments in the literature and further validated through a pilot test. The results reveal significant positive relationships between marketing capability and both product innovation and financial performance. However, the hypothesized relationship between product innovation and financial performance was not supported. These findings underscore the importance of investing in and enhancing marketing capabilities as a strategic imperative for SMEs seeking to drive innovation and achieve sustainable financial success.